Impact of the Moulding Parameters on Flowability of Bentonite-Bonded-Green Sand Mould - Abdulamer, Dheya (Archives of Foundry Engineering, 2026)
Compactability of the green sand, water content, and parameters of the moulding machine of the pressing speed, and compaction force have an influence on the sand moulding process. These parameters of the moulding machine and moulding material were examined to determine the appropriate factors to make bentonite-bonded green sand mould have a good flowability around the pattern. In the current work, flowability of the green sand was measured based on non-destructive flowability test using a new sand motion detection sensor flowability measurement during the pressing process of the green sand supports finding the optimal compaction time without wasting of the consumed energy for the compaction process. The results obtained of time-dependent-flowability shows that 26% compactability, and 4.17% water content gives highest flowability during compaction of the green sand by using 36 mm/s of the pressing speed. It was found that flowability of the green sand increases as a result of increasing of speed of the pressing machine.